Pro-mutagenic effects of the gut microbiota in a Lynch syndrome mouse model. (31st December 2022) - Pieters, Wietske; Hugenholtz, Floor; Kos, Kevin; Cammeraat, Maxime; Moliej, Teddy C.; Kaldenbach, Daphne; Klarenbeek, Sjoerd; Davids, Mark; Drost, Lisa; de Konink, Charlotte; Delzenne-Goette, Elly; de Visser, Karin E.; et al.
ABSTRACT: The gut microbiota strongly impacts the development of sporadic colorectal cancer (CRC), but it is largely unknown how the microbiota affects the pathogenesis of mismatch-repair-deficient CRC in the context of Lynch syndrome. In a mouse model for Lynch syndrome, we found a nearly complete loss of intestinal tumor development when animals were transferred from a conventional "open" animal facility to specific-pathogen-free (SPF) conditions. Using 16S sequencing we detected large changes in microbiota composition between the two facilities. Transcriptomic analyses of tumor-free intestinal tissues showed signs of strong intestinal inflammation in conventional mice. Whole exome sequencing of tumors developing in Msh2-Lynch mice revealed a much lower mutational load in the single SPF tumor than in tumors developing in conventional mice, suggesting reduced epithelial proliferation in SPF mice. Fecal microbiota transplantations with conventional feces altered the immune landscape and gut homeostasis, illustrated by increased gut length and elevated epithelial proliferation and migration. This was associated with drastic changes in microbiota composition, in particular increased relative abundances of different mucus-degrading taxa such as Desulfovibrio and Akkermansia, and increased bacterial-epithelial contact. Strikingly, transplantation of conventional microbiota increased microsatellite instability in untransformed intestinal epithelium of Msh2-Lynch mice, indicating that the composition of the microbiota influences the rate of mutagenesis in MSH2-deficient crypts.